ANALISIS EMOSI TOKOH UTAMA DALAM FILM PERAYAAN MATI RASA KARYA UMAY SHAHAB - Ameyliani Hasugian, Yosepha; Leo Shanty, Isnaini; Mustado, Maulida; Suhardi, Suhardi; Dwi Leoni, Tessa; Habibah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the emotions of the main character in Umay Shahab's film Perayaan Mati Rasa (Celebration of Numbness) using a literary psychology approach. The research focuses on how the main character's emotions are represented through the inner conflicts he experiences throughout the film. The method used is descriptive qualitative with content analysis techniques. The research data consists of dialogues, scenes, and expressions of the main character that contain emotional elements in the film Perayaan Mati Rasa. Data collection was carried out through observation and note-taking techniques, then analyzed based on David Krech's theory of emotions. The results of the study show that the emotions of the main character can be classified into seven indicators, namely guilt, pent-up guilt, self-punishment tendencies, shame, sadness, hatred, and love. These seven forms of emotion were found comprehensively and played an important role in building the main character's inner conflict in the film.